The Analysis of Learning Difficulties of Grade IV Primary School Students on The Material of The Collective Division Counting Operation - Mufidah, Siti; Alfan, Muhammad; Dewi, Radeni Sukma Indra (Faculty of Psychology, Universitas Medan Area, 2024)
Division arithmetic operations are one of the materials in elementary school mathematics lessons that students must learn. Division arithmetic operations in high classes are usually carried out using sequential division. The aim of this research is to describe students' learning difficulties in the division arithmetic operation material using a stacked method. The research method used is a qualitative method with a phenomenological approach. The data source in this research is class IV students at SD Negeri Bokor, Tumpang District. Data collection techniques use tests and documentation. The data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of the research show that students still experience difficulties in carrying out division calculation operations using a stacked method. Learning difficulties faced by students include weak mastery of prerequisite material, poor understanding of the concept of division and lack of skills in calculating division in descending order. The recommendation from this research is that there is further research as a solution to the problems found in this research.